Seasonal and interannual dissolved organic carbon transport process dynamics in a subarctic headwater catchment revealed by high-resolution measurements - Croghan, Danny; Ala-Aho, Pertti; Welker, Jeffrey; Mustonen, Kaisa-Riikka; Khamis, Kieran; Hannah, David M.; Vuorenmaa, Jussi; Kløve, Bjørn; Marttila, Hannu (2024)
Dissolved organic carbon (DOC) dynamics are evolving in the rapidly changing Arctic and a comprehensive understanding of the controlling processes is urgently required. For example, the transport processes governing DOC dynamics are prone to climate-driven alteration given their strong seasonal nature. Hence, high-resolution and long-term studies are required to assess potential seasonal and interannual changes in DOC transport processes. In this study, we monitored DOC at a 30 min resolution from September 2018 to December 2022 in a headwater peatland-influenced stream in northern Finland (Pallas catchment, 68° N). Temporal variability in transport processes was assessed using multiple methods: concentration–discharge (C–Q) slope for seasonal analysis, a modified hysteresis index for event analysis, yield analysis, and random forest regression models to determine the hydroclimatic controls on transport. The findings revealed the following distinct patterns: (a) the slope of the C–Q relationship displayed a strong seasonal trend, indicating increasing transport limitation each month after snowmelt began; (b) the hysteresis index decreased post-snowmelt, signifying the influence of distal sources and DOC mobilization through slower pathways; and (c) interannual variations in these metrics were generally low, often smaller than month-to-month fluctuations. These results highlight the importance of long-term and detailed monitoring to enable separation of inter- and intra-annual variability to better understand the complexities of DOC transport. This study contributes to a broader comprehension of DOC transport dynamics in the Arctic, specifically quantifying seasonal variability and associated mechanistic drivers, which is vital for predicting how the carbon cycle is likely to change in Arctic ecosystems.